دراسة العلاقة بين العمليات اللوجستية وجودة الخدمة المصرفية المقدمة "دراسة مسحية على المصارف العامة العاملة في الساحل السوري" (Latakia University Journal - Economic and Legal Sciences Series, 2018)
The aim of this study is to identify logistics and logistic management and its concept and to introduce the concept of quality of banking service. It also aims to analyze the relationship between logistics operations and the quality of banking service providedby public banks operating in the Syrian coast. In order to achieve this, the researcher identified and studied the dimensions of logistics management and its role in improving the quality of banking service provided, through a survey study where the research community included banks and customers of these public banks working in the Syrian coast. The most important thing is to find a significant relationship between the role of logistics operations (transport - storage - supply) and improve the quality of banking service in public banks operating in the Syrian coast. The researcher also presented a set of proposals and recommendations that are expected to help the public banks' administrations operating in the Syrian coast to achieve competitive advantage and gain customers satisfaction. The most important proposals: - Recommending the public banks in the Syrian coast to pay attention to the continuous improvement of the banking services provided. - Recommendation of the studied banks to possess an integrated transport fleet that meets the needs of customers with high quality. هدفت هذه الدراسة إلى التعرف على اللوجستيات والإدارة اللوجستية ومفهومها والتعريف بمفهوم جودة الخدمة المصرفية، كما تهدف الى تحليل العلاقة بين العمليات اللوجستية وجودة الخدمة المصرفية المقدمة من قبل المصارف العامة العاملة في الساحل السوري. ولتحقيق ذلك قام الباحث بتحديد ودراسة ابعاد الإدارة اللوجستية ودورها في تحسين جودة الخدمة المصرفية المقدمة، وذلك من خلال دراسة مسحية حيث تضمن مجتمع البحث على المصارف وعملاء هذه المصارف العامة العاملة في الساحل السوري. ومن أهم ماتم التوصل اليه وجود علاقة ذات دلالة بين دور العمليات اللوجستية (نقل-تخزين- توريد) وتحسين جودة الخدمة المصرفية في المصارف العامة العاملة في الساحل السوري. كما قدّم الباحث من خلال هذه الدراسة مجموعة من المقترحات والتوصيات التي من المتوقع أن تساعد إدارات المصارف العامة العاملة في الساحل السوري في تحقيق الميزة التنافسية وكسب رضا العملاء. ومن اهم المقترحات: - توصية المصارف العامة في الساحل السوري بالإهتمام بالتحسين المستمر للخدمات المصرفية المقدمة. - توصية المصارف المدروسة امتلاك اسطول نقل متكامل يلبي احتياجات الزبائن بجودة عالية.